Detecting Determinants of Low Non Performing Loans (Npl) Kupedes (A Study at PT. Bank Rakyat Indonesia (Persero), Tbk Sidoarjo Packaging Unit) - Adi Wicaksono (TRIGIN PUBLISHER, 2020)
This study aims to determine the determinants of the low non-performing loans of PT Bank Rakyat Indonesia (Persero), Tbk Sidoarjo Packaging Unit. This factor is seen from two sides, namely what strategy is applied by the management of PT Bank Rakyat Indonesia (Persero), Tbk Sidoarjo Packaging Unit and the motive behind the customer's willingness to pay smoothly. To obtain the above objectives, researchers used qualitative methods. Data obtained through interviews, documentation, and observation. From this study it was found that social capital plays a role in shaping the character of customers. This good character is able to make customers happy to fulfill their obligation to pay Kupedes installments. This type of social capital is social bounding, namely culture and culture, and social capital is of the type of social linking, namely networking. However, just like ivory, which always cracks, social capital also creates a mainstream that is different from the economic concept. Where for the economy, increasing capital through credit has an impact on increasing output, but the culture in the area of ​​debt customers is a disgrace. In addition to social motives, order to pay installments is based on economic motives, namely PBTW and fear of cutting off credit access. In addition to the motives of the customer, The strategy applied by PT BRI Packaging Unit to suppress NPL is in the management strategy in suppressing the emergence of NPL. This strategy starts from prevention efforts through strict selection by utilizing social capital in the form of networks with old debtors before the realization of this social capital which other banks do not have, considering that BRI has been operating for so long. After that, the next strategy is to monitor, develop and manage problematic Kupedes and even create a breakthrough in creating NPLs by increasing the outstanding credit realization, which is accompanied by the proactive work of line officials to collect non-performing loans in the following month. And of course, this is accompanied by the high level of professionalism and integrity of BRI officials in managing the loan portfolio.